A Green Theory Perspective on the Legal Personhood of the Whanganui River, New Zealand - Gertha Gultom; Yoga Ramadhani; Farisa Azzahra Abidin Putri; Amarillyn Narestara Khalisha Kandhi; Putri Alyaa Safira; Bintang Corvi Diphda (Universitas Darul Ulum, 2026)
This study addresses the global environmental crisis caused by modern anthropocentric paradigms that detach humans from nature, reducing ecological entities to mere commodities. It specifically explores the legislative transformation of the Whanganui River in New Zealand through the enactment of the Te Awa Tupua Act 2017. Utilizing Matthew Paterson’s Green Theory framework, this research examines how this landmark legal reform functions as a structural response to ecological degradation. Methodologically, this study is conducted as a qualitative case study that analyzes historical policies, colonial legal frameworks, and environmental conflicts within the Whanganui River system The principal conclusion demonstrates that by granting legal personhood to the river, the Te Awa Tupua Act 2017 offers a conceptual challenge to the deep structures of modernity, including the state system, capitalism, knowledge, and patriarchy. This shift from anthropocentrism to eco-centrism provides a pathway to reconstruct environmental governance, redistribute ecological risks, and serve as an influential model for global decolonization and ecological justice.